Genetics of migraine: where are we now - Grangeon, Lou; Lange, Kristin Sophie; Waliszewska-Prosół, Marta; Onan, Dilara; Marschollek, Karol; Wiels, Wietse; Mikulenka, Petr; Farham, Fatemeh; Gollion, Cédric; Ducros, Anne (The Journal of headaches and pain, 2023)
Migraine is a complex brain disorder explained by the interaction of genetic and environmental factors. In monogenic migraines, including familial hemiplegic migraine and migraine with aura associated with hereditary small-vessel disorders, the identified genes code for proteins expressed in neurons, glial cells, or vessels, all of which increase susceptibility to cortical spreading depression. The study of monogenic migraines has shown that the neurovascular unit plays a prominent role in migraine. Genome-wide association studies have identified numerous susceptibility variants that each result in only a small increase in overall migraine risk. The more than 180 known variants belong to several complex networks of "pro-migraine" molecular abnormalities, which are mainly neuronal or vascular. Genetics has also highlighted the importance of shared genetic factors between migraine and its major co-morbidities, including depression and high blood pressure. Further studies are still needed to map all of the susceptibility loci for migraine and then to understand how these genomic variants lead to migraine cell phenotypes.
Keywords: Migraine Disorders; Humans; migréna; Cortical Spreading Depression; lidé; Genome-Wide Association Study; Migraine with Aura; migréna s aurou; celogenomová asociační studie; šířící se kortikální deprese